The Expression of Emotions in the Spanish and Italian Filmic Audio Descriptions of The King’s Speech - Marra, Laura (Journal of Audiovisual Translation, 2023)
This paper puts forward a three-layered model for the analysis of linguistic items in filmic audio description (AD). The model is applied to three Spanish and Italian audio described scenes of the drama film The King’s Speech (Hooper, 2010). The aim is to evaluate lexical items that are chosen to verbalize information on characters’ emotional condition, or psyche. Verbs, nouns, adjectives, and adverbs used in the compared ADs will be analysed taking into consideration the communicative function(s) associated with each scene. The overall objective of the research is to shed light on the linguistic strategies that could potentially be used in AD to enhance the communicative value of the audiovisual source text, guiding the choice of informative or expressive rendering in AD to foster the audience’s engagement with the narrative. Results suggest that it might be useful to identify the communicative function of a given scene; this can turn into a valuable criterion, to be given due credit when creating AD. Lay summary In this article, we presented a model for the analysis of the words used in filmic audio description. Audio description is the verbal explanation of images or other elements which are difficult to grasp when it is not possible to access the visuals. We analysed the Italian and Spanish audio descriptions of three scenes from the drama film The King’s Speech (Hooper 2010). We focused on what types of verbs, nouns, adjectives and adverbs are used in the audio descriptions to talk about the characters’ emotions and disposition. We wanted to verify if the words used in the audio description scripts manage to reveal the hidden meanings expressed through images and sounds in each film scene. The model helped us to obtain initial results. We found that both the Spanish and Italian scripts prefer objective descriptions of the images, explaining the characters’ actions and reactions. At the same time, the Italian audio description tends to employ non-literal meanings, as shown by the use of some verbs in figurative senses and the inclusion of nouns that overtly refer to the character’s feelings. The study led us to conclude that, when the expression of emotions prevails in the film scene, it is crucial to determine which layer of meaning stands out in the scene, in order to choose the most appropriate words in audio description.